The Implementation of Course Review Hooray to Teach Vocabulary at Elementary School in Mojokerto - Islamica, Mutiara; Ganinda, Nurhayati; Mardiana, Wiwik (International Journal of Multilingual Education and Applied Linguistics, 2024)
This research aims to describe the implementation of the Course Review Hooray (CRH) method in teaching vocabulary and to see students' perceptions of the use Course Review Hooray (CRH) in their class. This research was based on the problem of students lack of vocabulary and motivation in learning vocabulary. The design of this research is qualitative approach. The Participants in this research were 28 students from the fourth grade of elementary school in Jrambe, Dlanggu, Mojokerto Regency. The data was collected through observation and questionnaires. The result of the first research question is the implementation of Course Review Hooray (CRH) in the classroom. There are fourth steps for the implementatition. The first, students are instructed to form groups with a total of 5 students in each group. Second, each group is given a card that is used to collect points. Third, when the teacher throws questions related to transportation material and if anyone can answer the question, the students raise their hands,and then they answer the question. Fourth, if the group's answer is correct, then 1 group cheered together “Hooraay” and followed by teacher giving points to the group's card in the form of a stamp. The group that gets the most points will get a reward at the end of the lesson. Based on the results of student perception from the implementation of Course Review Hooray (CRH), most of students feel this method is exciting, fun, the class atmosphere becomes lively, and they understand the material better if they use Course Review Hooray because it is challenging as they should collect points and they are actively involved in the learning process.